PENGURANGAN PAJAK DAN SOSIALISASI PENDAPATAN PAJAK PAJAK KENDARAAN BERMOTOR MELALUI KEPATUHAN WAJIB PAJAK - Pandapotan Ritonga; Dian Yustriawan; Tuti Anggreani; Yunita Aryanti (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2026)
Objective - This study aims to investigate and assess the impact of the Tax Amnesty Program and Tax Socialization on Motor Vehicle Tax Revenue and taxpayer compliance as a mediator. This quantitative study uses a questionnaire to collect information from 100 taxpayers. The data were analyzed using the SmartPLS 4.0 Structural Equation Model. Findings - This study concludes that the tax amnesty program is significantly influenced by revenue. Motor vehicle tax, tax socialization has a significant effect on motor vehicle tax revenue, the tax amnesty program does not have a significant effect on taxpayer compliance, tax socialization has a significant effect on taxpayer compliance, taxpayer compliance does not have a significant impact on motor vehicle tax revenue, tax amnesty program, and tax socialization do not have a significant impact on motor vehicle tax revenue through taxpayer compliance. Originality - This study investigates taxpayer issues that significantly and broadly affect motor vehicle tax revenue. This study also offers a deeper understanding of the relationship between the tax amnesty program, tax socialization, taxpayer compliance, and tax revenue..